STUDI PERBANDINGAN PROPIL TUMBUHAN AGROFORESTRY DI PERUM PERHUTANI DENGAN LAHAN MILIK DI KABUPATEN SUMEDANG - Ika Nofi Hastuti; Endang Sufiadi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2016)
The purpose of this research is to compare and described the profile of agroforestry plant which exists in Perum Perhutani KPH Sumedang and in land of society possession in Kabupaten Sumedang. Beside to know the factors which have influences on succeed of Agroforestry Program in Kabupaten Sumedang. The research locations are at 2 places. Tampomas Mountain Area and Geulis Mountain Area. This research perform for 3 (three) months, from September until the end of November 2013. The conclusion of this research is that agroforestry on land of society possession are dominated by Sengon (Paraserianthes falcataria) and Mahoni (Swietenia macrophylla). While the ground plants are dominated by Jahe and Suren (Toona sureni). Agroforestry land on Perum Perhutani are dominated by Pinus (Pinus merkusii) and Jati (Tectona grandis). While the ground plant are dominated by Jagung (Zea mays) and (Pennisetum purpureum). The succeed of Agroforestry Program in Kabupaten Sumedang are influenced by external factors (climate, pour of rain, moistness, land fertility, sunrise intensity, topography) and internal factors (seeds quality, seeds genetic, seeds provenance).